An F-Strain Mycoplasma gallisepticum Inoculation at Twelve Weeks of Age Does Not Modify the Effects of Fasting During Lay on the Blood Characteristics of Commercial Egg Laying Hens - Peebles , E.D.; Burnham, M.R.; Branton, S.L.; Gerard, P.D. (International Journal of Poultry Science, 2012)
The interactive effects of an F-strain Mycoplasma gallisepticum (FMG) inoculation at 12 wk of age with those of a 24 h fast during lay on the BW, mortality, egg production and blood characteristics of commercial egg laying hens at 34 and 46 wk of age were investigated. Blood parameters measured were whole blood hematocrit; plasma protein concentration (PP); serum total cholesterol, triglycerides and calcium concentrations; and percentage serum cholesterol recovered in very low, low and high density lipoprotein fractions. There were no interactive effects involving FMG inoculation and fasting (inoculation x fasting or age x inoculation x fasting) on any of the parameters investigated. These results suggest that a pre-lay (12 wk of age) FMG inoculation does not influence the effects of a 24 h fast during lay (34 and 46 wk of age) on the performance and blood characteristics of commercial layers.